The Web Based Ordering and Inventory Information System for Online Printing Services with TAM Method - Deana Novitasari; ardie halim wijaya (Tech-E, 2021)
In this digital era, it is easier for people to carry out all their activities with the help of technology, one of which is ordering activities. PT Media Langit Persada is a company engaged in digital printing where the ordering process is still done manually. For example customer must come to the printing house and make direct order transactions even the management division still doing data collection manually. This is considered less effective because it may causes many errors while storing data and the information obtained by the customer. This study aims to create a web-based ordering system that is expected to make it easier for customers to make ordering transactions while the company easier in managing other business processes. This system will later be tested using the Technology Acceptance Model (TAM) method which will determine whether this system is suitable for use and can be accepted by the community or not. This task can be done by distributing questionnaires to several prospective respondents who are considered to be contributing to this system.